مؤشرات رأس المال الاجتماعي لدى الأسرة: دراسة ميدانية على عينة من الأسر في المجتمع الليبي - عبدالقادر حسين, هند (مجلة كلية الاداب, 2024)
The study tried to identify the features of social capital in some of the Libyan families by identifying a number of indicators such as trust, participation, cooperation, cohesion, satisfaction, family and social relations, and the study relied on the case study based on the interview tool conducted on a number (10 Libyan families) with the husband and wife, and the results of the study showed that the nature of participation between members of the study sample of families appears in the form of three circles, where the images of participation between members of the same family increase, then It becomes less within the framework of the relationship with external groups of relatives and neighbors in the local community, to become less than that at the larger level, where the political participation of the individuals in the study sample decreases, and they also have the values of participation in the development of the local community, and the results of the study confirmed that trust levels decrease as we move away from the family, as trust in neighbors and relatives decreases from the family, and decreases more when dealing with state institutions, and the results of the analysis of interviews showed that there are positive trends At all levels (cooperation between family members, cooperation with relatives, as well as cooperation with neighbors), while the results of the study confirmed that most of the study sample realize the importance of family cohesion, which is reflected in attention to the needs of family members and cooperation in solving family problems.